Pneumococcal carriage among children under five in Accra, Ghana, five years after the introduction of pneumococcal conjugate vaccine - Nicholas T. K. D. Dayie; Elizabeth Y. Tettey; Mercy J. Newman; Elizabeth Bannerman; Eric S. Donkor; Appiah-Korang Labi; Hans-Christian Slotved (BMC, 2019)
Abstract Background The study objective was to determine the carriage and serotype distribution of Streptococcus pneumoniae among children in Accra, Ghana, five years after the introduction of the pneumococcal conjugate vaccine (PCV-13) in 2012. Methods Nasopharyngeal swab samples were collected from 410 children below 5 years of age in Accra, Ghana, from September to December, 2016. Pneumococcal isolates were identified by optochin sensitivity and bile solubility. Serotyping was performed using the latex agglutination kit and Quellung reaction. The isolates were furthermore tested for antimicrobial susceptibility for different antimicrobials, including penicillin (PEN). Twelve isolates including seven non-typeable (NT) isolates were characterized using whole-genome sequencing analysis (WGS). Results The overall carriage prevalence was found to be 54% (95% CI, 49-59%), and 20% (95% CI, 49-59%) of the children were carrying PCV-13 included serotypes, while 37% (95% CI, 33-42%) of the children were carrying non-PCV-13 serotypes. Based on the serotype distribution, 33% of all observed serotypes were included in PCV-13 while 66% were non-PCV-13 serotypes. The dominating non-PCV-13 serotypes were 23B, 16F, and 11A followed by PCV-13 serotypes 23F and 19F. The PCV-13 covers the majority of resistant isolates in Accra. A proportion of 22.3% of the isolates showed intermediate resistance to penicillin G, while only one isolate showed full resistance. Forty-five isolates (20.5%) were defined as multidrug-resistant (MDR) as they were intermediate/resistant to three or more classes of antimicrobials. Of the seven NT isolates characterized by WGS, four showed highest match to genotype 38, while the remaining three showed highest match to genotype 14. Four MDR serotype 19A isolates were found to be MLST 320. Conclusion PCV-13 introduced in Ghana did not eliminate PCV-13 covered serotypes, and the carriage rate of 54% in this study is similar to carriage studies from pre PCV-13 period. However, the penicillin non-susceptible isolates have been reduced from 45% of carriage isolates before PCV-13 introduction to 22.3% of the isolates in this study. Continuous monitoring of serotype distribution is important, and in addition, an evaluation of an alternative vaccination schedule from 3 + 0 to 2 + 1 will be important to consider.